Deep‐UV Light‐Emitting Based on the hBN:S/hBN: Mg Homojunction - Ransheng Chen; Qiang Li; Wannian Fang; Qifan Zhang; Jiaxing Li; Zhihao Zhang; Kangkang Liu; Feng Yun; Yanan Guo; Tao Wang; Yue Hao (Advanced Science)
Abstract A hexagonal boron nitride (hBN) based p‐n homo‐junction is expected to demonstrate a great potential for being fabricated into an emitter (either light‐emitting diode or laser diode) in the deep‐UV spectral region. However, it remains a great challenge to achieve n‐type conductive hBN. Herein, n‐type hBN is obtained by means of doping sulfur into hBN. The structure and the electric properties of S‐doped hBN is studied via density functional theory, indicating that the orbital coupling between S 3p and B 2p orbital introduces shallow donor energy levels. The S atoms in the multilayer structure demonstrate enhanced electron delocalization compared with its mono‐layer counterpart, suggesting that multilayer hBN:S is more inclined to be n‐type conductive than its mono‐layer counterpart. Experimentally, a multilayer hBN:S sample is successfully grown on sapphire substrates, where the S content, up to 1.21%, is obtained. The hBN:S film shows an in‐plane current of 1.6 nA using Ti as ohmic contact and 8.4 nA using Ni as Schottky contact, respectively. The donor level induced by the S atoms is located at 0.349 eV below the CBM. Finally, a vertically‐stacked n‐hBN/p‐hBN (hBN:S/hBN: Mg) structured junction is grown, and demonstrating a promise for being fabricated into a deep‐UV emitter.